Alteração hidrotermal e metalogênese do depósito paleoproterozóico Au ± Cu do Basílio, Província Aurífera de Alta Floresta (MT), Cráton Amazônico - Bressan, Rafaela Santo Olaia [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Alta Floresta Gold Province, is located in the south-central Amazon Craton and belongs to the northern portion of the state of Mato Grosso. The Province consists essentially of plutono-volcanic suites of paleoproterozoic age and is associated to a sedimentary coverage. It hosts more than a hundred gold deposits aligned according to the Peru-Trairão alignment. The primary mineralizations of the province can be divided into three groups: (I) Au ± Cu (± Bi ± Te ± Ag) disseminated; (II) Au ± Cu confined in granite systems; (III) Au + Zn + Pb ± Cu ± Mo. The mineralizations of type (I) and (II) were interpreted as Au-porphyry type systems while type (III) was interpreted as an epithermal system of low to intermediate sulfation. In this context, the Paleoproterozoic deposit of Au ± Cu do Basílio, is located in the city of Novo Mundo and belongs to group (II). The Basilio corresponds to a deposit still unpublished in the region and, therefore, used as a case study in this work. To get the data, the sample collection and systematic description of the samples were used as methodology. Subsequently, the petrographic characterization of the hosts, typologies, styles and paragenesis of hydrothermal alterations were carried out, as well as the style and paragenesis of the ore of Alvo Basilio. The lithotypes found have a extensive hydrothermal alterations: such as sodic, potassic, sericitic, chloritic, propylitic, silicification, and late venules. The mineralized zones of this deposit are spatially and genetically related to representative changes in alkaline pH and low temperature conditions. The ore is also associated to stages of hydrothermal alteration saturated in silica and to the chloritization. The disseminated ore is represented by chalcopyrite + pyrite ± magnetite ± galena, while the venular is dominated by pyrite ± chalcopyrite ± magnetite ± galena ± gold. The gold has concentrations of 68% of gold, 22% of silver and...

A Província Aurífera de Alta Floresta (PAAF) está situada no centro-sul do Cráton Amazônico e está localizada na porção norte do estado do Mato Grosso. Geologicamente, a Província é constituída essencialmente por suítes plutono-vulcânicas de idade paleoproterozóica e coberturas sedimentares associadas. Hospeda mais de uma centena de depósitos auríferos alinhados segundo o Alinhamento Peru-Trairão. As mineralizações primárias da província podem ser divididas em três grupos: (I) Au ± Cu (± Bi ± Te ± Ag) disseminado; (II) Au ± Cu confinados em sistemas graníticos; (III) Au + Zn + Pb ± Cu ± Mo. As mineralizações do tipo (I) e (II) foram interpretadas como sistemas do tipo Au-pórfiro enquanto o tipo (III) foi interpretado como um sistema epitermal de baixa a intermediária sulfetação. Neste contexto, o depósito filonar paleoproterozóico de Au ± Cu do Basílio, está localizado no município de Novo Mundo e é pertencente ao grupo (II). Corresponde a um depósito ainda inédito na região e, portanto, utilizado como estudo de caso neste trabalho. Para a obtenção dos dados utilizou-se como metodologia a coleta de amostras e descrição sistemática das mesmas. Posteriormente foram realizadas as caracterizações petrográficas das hospedeiras, das tipologias, estilos e paragêneses das alterações hidrotermais, além de definido o estilo e paragênese do minério do Alvo Basílio. Os litotipos encontrados apresentam alterações hidrotermais abrangentes, a exemplo das alterações: sódica, potássica, sericítica, clorítica, propilítica, silicificação, bem como por alterações com ocorrência subordinada, representadas por venulações tardias. As zonas mineralizadas desse depósito encontram-se espacial e geneticamente relacionadas a alterações representativas de condições de pH alcalino e temperaturas baixas, bem como associadas a estágios de alteração...
Keywords: Mineralogia; Alteração hidrotermal; Metalogenia; Crátons; Ouro - Minas e mineração; Alta Floresta (MT)